DEVELOPMENT OF EARLY CHILDREN'S LANGUAGE ABILITY THROUGH CHAIN WHISPER PLAY METHOD AT KASIH BANGSA PALU KINDERGARTEN - Rumandjo, Nurliyana; Dyantari, Putu; Putra, Gusti Ngurah (STAH Dharma Sentana Sulawesi Tengah, 2023)
Language skills are a very important aspect in early childhood development. Language skills are a means for thinking, a means for listening, a means for speaking and a means for children to be able to read and write. It is on this basis that this research was carried out with the problem of how to develop early childhood language skills through the chain whisper play method and what are the advantages and disadvantages of developing language skills through the chain whisper play method. This research aims to describe the development of early childhood language skills through the chain whisper play method. This research uses a qualitative approach, data collection techniques through observation, interviews and documentation. From the results of the research conducted, it can be concluded that developing language skills can be done by introducing game steps according to the learning theme. Meanwhile, the disadvantage of the chain whispering method in efforts to develop early childhood language is that it creates a noisy classroom atmosphere, secondly, it requires quite a long time.